Push-Out Bond Strength, Characterization, and Ion Release of Premixed and Powder-Liquid Bioceramic Sealers with or without Gutta-Percha - Retana-Lobo, Cristina; Tanomaru-Filho, Mario [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP]; Benavides-García, Marianella; Hernández-Meza, Erick; Reyes-Carmona, Jessie (Hindawi, 2021)
Objective. To evaluate the push-out bond strength of premixed and powder-liquid bioceramic sealers with or without gutta-percha (GP) cone. Materials and Methods. Radicular dentin samples were prepared from 80 single-rooted human teeth. After root canal preparation using ProTaper® and irrigation with NaOCl and EDTA, teeth were divided according to the root canal sealer (n=20): AH Plus®, EndoSequence® BC Sealer™, ProRoot® Endo Sealer, and BioRoot™ RCS. Samples were randomly divided into two subgroups (n=10): GP-S: root canal filling using the single-cone technique, or S: filling with only sealer. Specimens were kept at 37°C and 100% humidity in calcium-free PBS for 30 days. The push-out bond strength was measured in MPa. Fractured specimens were observed at 25x to evaluate the type of failure. pH and calcium ion release were measured at different experimental periods. Raman and SEM-EDAX analyses were performed for root canal sealers. Data were analysed using three-way analysis of variance (ANOVA) and post hoc Tukey test at a significance of P<0.05. Results. Push-out bond strength was greater for samples obturated with only sealers (S) than samples obturated with the single-cone technique (GP-S) (P<0.05). BioRoot™ RCS had greater bond strength than EndoSequence® BC Sealer™. Adhesive failures between cement and gutta-percha cone (87.5%) were predominant in the GP-S. Cohesive failures were predominant for S (80%). BioRoot™ RCS and ProRoot® ES presented higher alkalinization potential than the premixed sealer (EndoSequence® BC Sealer™). Powder-liquid bioceramic sealers (BioRoot™ RCS and ProRoot® ES) released the highest cumulative amount of calcium (28.46 mg/L and 20.05 mg/L). Conclusion. Push-out test without gutta-percha cone presents higher bond strength for bioceramic sealers. Powder-liquid calcium silicate-based sealers present greater bioactivity related to alkalinization potential and calcium ion release.